The impact of financial leverage on firm performance: A case of construction firms in Vietnam - Le, Thai Phong (Journal of International Economics and Management, 2016)
The debt situation of Vietnam construction sector is analyzed by the study. Construction firms in Vietnam are very familiar with using debt. They diversify their capital structure by 7:3 or 70% of leverage and 30% of owners’ equity.In spite of the high financial leverage rate, the increase in sales revenue and the ability to liquidate current debts, the profitability, return on equity rate and book value decreased considerably. With the sample of 45 listed construction companies in Vietnam, this paper analyzes the effects of financial leverage on financial performance of construction industry in Vietnam from 2007 to 2011. GLS estimation has been carried out to analyze the relationship between financial leverage and financial performance in Vietnam construction industry during five years from 2007 to 2011. From the results, the financial leverage is positively correlated to return on equity, earnings per share, and negatively related to return on asset and quick ratio...